2022
DOI: 10.3389/fmicb.2022.831655
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Multidrug Resistance With Antimicrobial Peptide-Decorated Nanoparticles and Polymers

Abstract: As a category of small peptides frequently found in nature, antimicrobial peptides (AMPs) constitute a major part of the innate immune system of various organisms. Antimicrobial peptides feature various inhibitory effects against fungi, bacteria, viruses, and parasites. Due to the increasing concerns of antibiotic resistance among microorganisms, development of antimicrobial peptides is an emerging tool as a favorable applicability prospect in food, medicine, aquaculture, animal husbandry, and agriculture. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 184 publications
1
8
0
Order By: Relevance
“…Compared to the Blank B group without bacteria, the size of the tumors in the Blank C group with bacteria increased by 57.3%, and a large number of live St. pneumoniae were detected (Figure C–E). These results demonstrated the successful building of the model and suggested that St. pneumoniae promoted the proliferation of tumor cells and produced oncogenes, as reported previously. ,, Additionally, MSNs showed negligible effects on the tumor and bacteria. Compared to Blank C, both free DOX and MSN@DOX inhibited tumor proliferation and tumor sizes decreased by 45.4% and 68.4% (Figure C,D), respectively.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Compared to the Blank B group without bacteria, the size of the tumors in the Blank C group with bacteria increased by 57.3%, and a large number of live St. pneumoniae were detected (Figure C–E). These results demonstrated the successful building of the model and suggested that St. pneumoniae promoted the proliferation of tumor cells and produced oncogenes, as reported previously. ,, Additionally, MSNs showed negligible effects on the tumor and bacteria. Compared to Blank C, both free DOX and MSN@DOX inhibited tumor proliferation and tumor sizes decreased by 45.4% and 68.4% (Figure C,D), respectively.…”
Section: Resultssupporting
confidence: 85%
“…These results demonstrated the successful building of the model and suggested that St. pneumoniae promoted the proliferation of tumor cells and produced oncogenes, as reported previously. [22][23][24]50,51 Additionally, MSNs showed negligible effects on the tumor and bacteria. Compared to Blank C, both free DOX and MSN@DOX inhibited tumor proliferation and tumor sizes decreased by 45.4% and 68.4% (Figure 5C,D), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The release rate of polymeric nanoparticles is dependent on polymer characteristics, process conditions, and peptide properties and is produced by using various techniques. AMPs can be converted into prodrugs by covalently bonding them to synthetic polymers via labile bonds . Microneedles made from polymers embedded with AMPs can be used to deliver AMPs to the wound site.…”
Section: Different Biomaterial-based Approaches In Transdermal Delive...mentioning
confidence: 99%